Rheological properties and fluid dynamics of egg yolk - Telis-Romero, J.; Thomaz, CEP; Bernardi, M.; Telis, VRN; Gabas, A. L. (Elsevier B.V., 2006)
The rheological behavior of egg yolk was studied at a range of temperatures (277-333 K) using a concentric cylinder viscometer. Rheological behavior was pseudoplastic and flow curves fitted by the power law model. The consistency and behavior indexes, dependent on temperature, were expressed by an Arrhenius-type equation. The rheological parameters, together with experimental values of pressure loss in tube flow were used to calculate friction factors. The good agreement between predicted and observed values confirmed the reliability of the equations proposed for describing the flow behavior of the egg yolk. (c) 2005 Published by Elsevier Ltd.
Keywords: pseudoplastic; power law model; non-Newtonian fluid; friction factor